PERKEMBANGAN HIV DAN AIDS DI INDONESIA: Tinjauan Sosio Demografis - Sri Sunarti Purwaningsih; NFN Widayatun (Jurnal Kependudukan Indonesia, 2008)
HIV-AIDS epidemic in Indonesia growsfastly and spread out to all over provinces in Indonesia, especially among some high risk populations such as commercial sex workers and injecting drug users (IDUs). In 200 /the accumulative HIV-AIDS cases in Indonesia was 2575, then increased to 6789 in Maret 2005 and reached the number of I 8963 in June 2008. The number is assumed to be much higher that the official reported cases as the existence of iceberg phenomenon. This paper aimed at presenting the spread of HIV-AIDS cases in Indonesia from socio-demographic point of views. The data used for this paper was mainly taken from the result of literature review as well as our research conducted in Surabaya and Bali in /999 and from our recent study conducted in Batam and Sanggau in 2006 and 2007. Data collection was done by the use of indepth interviews, focus group discussion and field observation. The study shows that HIV-AIDS cases have steady increased among particular groups, such as women and those in the age group of /5-39 years. The highest number of AIDS cases was found among people at the 15-19 years age group. The increased cases were mainly due to the high-risk behaviour that exposed to the spread of HIV-AIDS such as the use of unsafe injecting drug and sexual practices. This study recommends that HIV-AJDS problem has to be overcome immediately and pay special attention to the most affected age groups for targeting as well as introducing type of interventions.Keywords: spread of HIV-AIDS cases, socio demograhic factors, risk behaviour